2008
DOI: 10.18222/eae193920082474
|View full text |Cite
|
Sign up to set email alerts
|

Crianças Contaminadas por Chumbo: estudo comparativo sobre desempenho escolar

Abstract: ResumoPesquisas mostram que a presença de metais, acima dos níveis permitidos pela legislação, representa riscos para a saúde humana. Crianças são mais vulneráveis aos efeitos do chumbo, que pode causar rebaixamento permanente da inteligência e outros distúrbios associados, como baixo desempenho escolar. O objetivo do estudo foi avaliar o rendimento escolar de crianças contaminadas por chumbo, comparando-o com o daquelas que não estavam contaminadas. Participaram três grupos com 25 crianças cada, de seis a tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…A study that assessed 20 children with lead poisoning, aged three to six years, found immediate memory alteration in 65% of children 35 . When assessing 25 school-age children (six to thirteen years) through the Academic Performance Test, one study found better performance children not contaminated by lead and worse performance in children with lead poisoning 36 .…”
Section: Discussionmentioning
confidence: 99%
“…A study that assessed 20 children with lead poisoning, aged three to six years, found immediate memory alteration in 65% of children 35 . When assessing 25 school-age children (six to thirteen years) through the Academic Performance Test, one study found better performance children not contaminated by lead and worse performance in children with lead poisoning 36 .…”
Section: Discussionmentioning
confidence: 99%
“…3, it is possible to observe that the concentrations of metals Zn, Mn, and Ba are below the limit for discharges of treated effluent in class II water bodies, as opposed to Al, Cu, and Fe that are above the maximum limit allowed for output (CONAMA 2005). Metals with concentrations above the permitted levels imply a greater concern due to the great toxicological potential of these elements, which can compromise human health, being its accumulation risk factor for a series of diseases from nausea to heart disease, Alzheimer's disease, and cancer (Campbell 2002;Capellini et al 2008;CETESB 2013). On August 7, one can see high amounts of some metals (Zn, Mn, Al, Cu, and Fe) only at ETECan.…”
Section: Metal Concentrationmentioning
confidence: 99%
“…Lead (Pb) can affect almost all organs, with the central nervous system being the most sensitive in both children and adults. The main effects of exposure to Pb are weakness, irritability, nausea, abdominal pain, and anemia (Capellini et al 2008;CETESB 2013). Copper (Cu) and zinc (Zn) are essential elements for living organisms; however, the ingestion of water containing high concentrations of these metals can produce nausea, vomiting, abdominal pain, and diarrhea, especially in children (CETESB 2013).…”
Section: Introductionmentioning
confidence: 99%
“…É utilizado na produção de ligas (bronze e latão), PVC, borrachas, vidros, cabos elétricos, soldas de peças, chapas elétricas e na fabricação e recuperação de baterias (GRIGOLETTO, 2011). No solo a concentração de Pb varia, sendo mais elevada em regiões industriais e de tráfego intenso do que em regiões isoladas (CAPELLINI et al, 2013). A contaminação do solo por Pb ocorre quando a quantidade do metal no ambiente supera a capacidade do solo em retê-lo, podendo ser absorvido pelas plantas ou carreado para os lençóis freáticos, contaminando as águas (FERNANDES et al, 2011).…”
Section: Introductionunclassified